METODE PEMBIASAAN SHOLAT DHUHA BERJAMAAH DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MEMBENTUK KARAKTER RELIHIUS SISWA DI TAMAN KANAK-KANAK ‘AISYIYAH BUSTANUL ATHFAL 8 KEPANJEN - Agustin, Alif Achadah, Hasan Bisri (PRODI PAI FIK UNIRA MALANG, 2024)
This research was motivated by efforts to form students' religious character through the method of getting used to dhuha prayers in congregation at the 'Aisyiyah Bustanul Athfal 8 Kepanjen Kindergarten. Researchers have encountered many factors, such as currently many students behave less politely towards teachers. So, to minimize this problem, researchers used the method of getting used to Duha prayers in congregation in order to improve the religious character of the students at Kindergarten 'Aisyiyah Bustanul Athfal 8 Kepanjen who are good and have noble morals. From the results of this research, it can be seen that the method used is the method of getting used to the morning dhikr prayer, Asmaul Husna and the method of providing an understanding of the importance of praying. The strategies used by teachers in carrying out the Dhuha prayer habituation method are inviting, understanding, teaching, giving examples, giving evaluations and evaluating or giving direction to students. The impact of students on the process of getting used to dhuha prayer makes them individuals who have a sense of gratitude and provide positive expressions such as discipline in prayer.